The Weakness Function of Political Recruitment, Leader Regeneration in Local Head Election - Nawang Retno Dwiningrum (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2017)
Political recruitment is one of the political parties functions that should be performed by a political party that could generate the future leaders. Weak cadre in political parties is seen in local elections, the party can not nominate its cadres themselves as a local head candidate, it is caused by the function of political recruitment that not worked properly, because the management of political parties are not work well, their work program that does not run and the lack of availability funds for their political party to do the political recruitment.Keywords: political recruitment, regeneration and the local head elections